The Motivation of Socialite Women in Hanging Out in Cafes - Firdaus W Suhaeb,; Ernawati S. Kaseng, (Technium Social Sciences Journal, 2023)
This study aims to describe and analyze the motivation of socialite women hanging out in cafes and the impact of these lifestyles. The type of research used in this article is descriptive-qualitative. Research locus in Rappocini District, Makassar City. Research informants are chosen deliberately. Meanwhile, data collection techniques in this study are through observation, interviews, and documentation. Data analysis techniques use qualitative descriptive analysis and then data validation to test the correctness of the data that has been found through triangulation. The findings of this article research are known that the lifestyle motives of socialite women hanging out in cafes are influenced by internal motives such as; attitudes, personality, self-concept, perceptions, and experiences and observations, while external motives such as; reference groups, families, and social classes. The positive impact of the lifestyle of socialite women hanging out in cafes, such as being able to increase solidarity and having the ability to socialize. As for the negative impact of the lifestyle of socialite women hanging out in cafes, such as wasted time and becoming more wasteful in terms of finances.